Efficacy of Selected Biopesticides as Protectants Against Dermestes maculatus on Smoked Clarias gariepinus and Oreochromis niloticus in Wukari Metropolis, Taraba State - Alase N.; Okrikata E.; Tidi J. A. (Kwaghe International Journal of Sciences and Technology, 2026)
Fish is an affordable source of animal protein and is increasingly utilized to address nutritional deficiencies in tropical regions; however, post-harvest losses caused by insect infestation remain a major challenge to its preservation and utilization. This study aimed to assess the repellent effects of selected biopesticides against adult D. maculatus on smoked fish and to determine their effects on weight loss in smoked fish infested with the pest. Three newly emerged adult insects were introduced into transparent containers containing fish samples admixed with powders of C. annuum, P. guajava leaves, and C. papaya leaves at concentrations of 5.0 g, 7.0 g, and 10 g per 15 ± 5 g of fish. The results showed that the highest mean percentage repellency of adult D. maculatus on smoked catfish was recorded with 10 g of C. annuum powder, yielding 99.92 ± 0.00%, whereas the lowest mean percentage repellency was observed with 5 g of C. papaya powder, with a value of 0.08 ± 0.00%. Overall, C. annuum powder at all tested concentrations demonstrated the greatest repellent effect, while C. papaya showed the lowest repellency among the three plant treatments. The findings further indicated that, for most observation periods, increasing the concentration of plant treatment tended to reduce weight loss in tilapia, although this pattern was not entirely consistent; conversely, weight loss generally increased with longer storage duration at each treatment concentration. The study concludes that the tested biopesticides have potential as alternatives to synthetic pesticides for the control of Dermestes maculatus infestation in smoked fish, with C. annuum showing the greatest promise for enhancing protection and reducing post-harvest losses.